A new strain of Chino del Tomate Virus isolated from soybean plants (Glycine max L.) in Mexico - Mauricio-Castillo, Jorge Armando; Argüello-Astorga, Gerardo Rafael; Bañuelos-Hernández, Bernardo; Ambríz- Granados, Salvador; Velásquez-Valle, Rodolfo; Méndez-Lozano, Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
Molecular techniques such as PCR and RFLP allowed theisolationandidentificationofcompleteAcomponent sequences of two begomoviruses from soybean plants with virus symptoms in the state of Sinaloa, Mexico. Both genomes were analyzed by comparison of their nucleotide sequences with those available in the NCBI database. The first isolate corresponded to Rhynchosia golden mosaic virus (RhGMV), while the second corresponded to the Chino del tomate virus (CdTV) which showed a 92.3% overall identity with its closest relatives, CdTV-[8] and CdTV-[RK]. Plant extracts of symptomatic soybean were analyzed by PCR using a pair of universal primers that allowed to amplify and confirm the presence of the CdTV B component, therefore the second isolate identified in this work is proposed as a new CdTV strain called "Chino del tomate virus - Soybean" (Mexico: Sinaloa: 2005). The presence of this new CdTV strain isolated from soybean is important because to date virus infection was naturally restricted to plants of the Solanaceae family.
Keywords: geminivirus; mixed infection; soybean; RFLP; CdTV